Conservation, Extensive Heterozygosity, and Convergence of Signaling Potential All Indicate a Critical Role for KIR3DL3 in Higher Primates - Leaton, Laura A.; Shortt, Jonathan; Kichula, Katherine M.; Tao, Sudan; Nemat-Gorgani, Neda; Mentzer, Alexander J.; Oppenheimer, Stephen J.; Deng, Zhihui; Hollenbach, Jill A.; Gignoux, Christopher R.; Guethlein, Lisbeth A.; Parham, Peter; et al. (Frontiers in Immunology, 2019)
Natural killer cell functions are modulated by polymorphic killer cell immunoglobulin-like receptors (KIR). Among 13 human KIR genes, which vary by presence and copy number, KIR3DL3 is ubiquitously present in every individual across diverse populations. No ligand or function is known for KIR3DL3, but limited knowledge of expression suggests involvement in reproduction, likely during placentation. With 157 human alleles, KIR3DL3 is also highly polymorphic and we show heterozygosity exceeds that of HLA-B in many populations. The external domains of catarrhine primate KIR3DL3 evolved as a conserved lineage distinct from other KIR. Accordingly, and in contrast to other KIR, we show the focus of natural selection does not correspond exclusively to known ligand binding sites. Instead, a strong signal for diversifying selection occurs in the D1 Ig domain at a site involved in receptor aggregation, which we show is polymorphic in humans worldwide, suggesting differential ability for receptor aggregation. Meanwhile in the cytoplasmic tail, the first of two inhibitory tyrosine motifs (ITIM) is conserved, whereas independent genomic events have mutated the second ITIM of KIR3DL3 alleles in all great apes. Together, these findings suggest that KIR3DL3 binds a conserved ligand, and a function requiring both receptor aggregation and inhibitory signal attenuation. In this model KIR3DL3 resembles other NK cell inhibitory receptors having only one ITIM, which interact with bivalent downstream signaling proteins through dimerization. Due to the extensive conservation across species, selection and other unusual properties, we consider elucidating the ligand and function of KIR3DL3 to be a pressing question.